Intersectional feminist criminology: A critical companion to theory and research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice. Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic. Critical perspectives on the topic. Critical thinking breaks. Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system. © 2025 by Venezia Michalsen. All rights reserved.
Keywords: dept.soc

Intersectional Feminist Criminology: A Critical Companion to Theory and Research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice.   Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic Critical perspectives on the topic Critical thinking breaks Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system.
Keywords: dept.soc

The role of power in community participation: Relocation as climate change adaptation in Fiji - Bertana, Amanda (Environment and Planning C: Politics and Space, 2020)
As the impacts of climate change intensify, potential relocation is becoming more of a reality for coastal communities throughout the world. This is furthering the demand for the implementation of governance relocation frameworks. In order to stay true to the principles of environmental justice while at the same time ensuring an effective policy that meets the needs and wants of affected communities, an adaptive relocation framework requires collaboration between state and non-state actors. It is thus important to pay attention to how non-state actors are incorporated into public participatory climate change adaptation efforts. In order to affectively address previous limitations of public participation, stakeholders must pay attention to already existing power systems. Through a case study approach of a village relocation project in Fiji, I examine the role of power in a climate change adaptation plan that involved the community of Vunidogoloa, local government, and national government stakeholders. I employ Steven Lukes’s three-dimensional framework of power to the case of Vunidogoloa, a Fijian village that relocated inland due to coastal erosion and shoreline flooding, to illustrate how the political arrangement of participation reinforced existing hierarchies between the village and the government.
Keywords: dept.soc; peer-reviewed

Religious Explanations for Environmental Degradation in Narikoso, Fiji - Bertana, Amanda (Understanding Climate Change through Religious Lifeworlds, 2021)
How can religion help to understand and contend with the challenges of climate change?Understanding Climate Change through Religious Lifeworld,edited by David Haberman, presents a unique collection of essays that detail how the effects of human-related climate change are actively reshaping religious ideas and practices, even as religious groups and communities endeavor to bring their traditions to bear on mounting climate challenges.People of faith from the low-lying islands of the South Pacific to the glacial regions of the Himalayas are influencing how their communities understand earthly problems and develop meaningful responses to them. This collection focuses on a variety of different aspects of this critical interaction, including the role of religion in ongoing debates about climate change, religious sources of environmental knowledge and how this knowledge informs community responses to climate change, and the ways that climate change is in turn driving religious change.Understanding Climate Change through Religious Lifeworlds offers a transnational view of how religion reconciles the concepts of the global and the local and influences the challenges of climate change.
Keywords: dept.soc

Imprisoned: Interlocking Oppression in Law Enforcement, Housing, and Public Education - Meyerhoffer, Cassi A.; Rodriguez, Brittany Leigh (University of Georgia Press, 2023)
Over the last several years, the United States has experienced a surge in bystander videos that have captured incidents of police brutality and prejudice directed largely at Black people. Public outrage surrounding police brutality persists as these incidents continue to reach the public eye. As public discourse around police brutality and racial inequality largely centers on specific events, there is a dearth of information about systemic racism and how race and racism pervade every single aspect of American life. How Black people are often treated by law enforcement is reflective of larger historical racial inequities and injustices that extend far beyond the criminal justice system and intersect with how Black people access housing, occupy public spaces, and are treated in American public schools.Imprisoned: Interlocking Oppression in Law Enforcement, Housing, and Public Educationfocuses on contemporary systemic racism as it relates to how the U.S. criminal justice system, housing system, and education system intersect to create a matrix of inequality for Black people. To illustrate the systemic nature of racism in American policing and communities, this book highlights contemporary policies and practices that intersect with residential segregation and public schooling that continue to affect Black people on a large-scale, structural level―demonstrating the extent to which the United States criminal justice system is tied to where people live and how they are treated and educated in public schools.
Keywords: dept.soc

Race: Readings on Identity, Ideology, and Inequality - Meyerhoffer, Cassi (Cognella anthology series for teaching, 2021)
Keywords: Race awareness; Race relations; United States; Racism; United States; United States; dept.soc; faculty_collection

Poverty, Racism, & Sexism: The Reality of Oppression in America - Doob, Christopher Bates (Routledge, Taylor & Francis Group, 2021)
"Exploring the structural causes and consequences of inequalities based on a person's race, class, and gender, Poverty, Racism & Sexism: The Reality of Oppression in America concentrates on this formidable set of disadvantages, demonstrating how Americans are adversely affected by just one or a combination of three social factors. Grounded in sociological thought, the text highlights unfolding stories about major social inequalities and relentless campaigns for people's rights. Weaving together such concepts as individualism, social reproduction, social class, and intersectionality, the book provides a framework for readers to understand the vast injustices these groups encounter, where and why they originated, and why they continue to endure. Poverty, Racism & Sexism is a compact, versatile volume which will prove an invaluable resource for those studying social inequality, social problems, social stratification, contemporary American society, social change, urban sociology, and poverty and inequality"--
Keywords: Equality; Race relations; United States; Poverty; United States; Racism; United States; Sexism; United States; United States; dept.soc; faculty_collection

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed

“On the street, the only person you gotta bow down to is yourself”: Masculinity, homelessness, and incarceration - Umamaheswar, Janani (Justice Quarterly, 2021)
Despite the well-established link between homelessness and incarceration, very little qualitative research has focused on the social processes that underlie this nexus. In this article, I draw on 19 in-depth interviews with incarcerated men who reported pre-prison housing instability, supplemented with 5 interviews with formerly-incarcerated men experiencing homelessness, to explore the gendered nature of the homelessness-incarceration nexus. I propose the concept of “liberative instability”—defined as an unfettered lifestyle characterized by double-edged freedom and independence—to explore the changing meaning of homelessness in men’s narratives of their life course. Additionally, I explore how themes of masculinity and liberative instability are embedded in men’s narratives of freedom and confinement as they reflect on their experiences with homelessness and incarceration. These findings animate existing quantitative research by highlighting that the homelessness-incarceration nexus cannot be understood fully or disrupted without considering the significance of age-graded cultural scripts regarding masculinity. © 2021 Academy of Criminal Justice Sciences.
Keywords: Homelessness; dept.soc; incarceration; masculinity; peer-reviewed; the life course

Gender-collaborative training in elite university sport: Challenging gender essentialism through integrated training in gender-segregated sports - Ogilvie, M. F.; McCormack, Mark (International Review for the Sociology of Sport, 2020)
Competitive teamsport at university level is predominantly segregated by gender in many western countries, despite concerns that gender segregation in sport can perpetuate sexism and gender inequality. While policies and activities seek to challenge sexism and gender inequality, the use of gender collaboration within a gender-segregated system as a method to achieve this has received little attention. In this article, we draw on a year-long ethnography of elite sport and 48 in-depth interviews with elite male and female athletes at a British university to explore the impact of various forms of gender mixing during training, which we call ‘gender-collaborative training’. While men’s and women’s teams competing against each other in practice matches resulted in gender-essentialist narratives attributing difference to biology, gender-integrated practices and workouts provided opportunities for men and women to train together without the gendered sport-specific associations that can reproduce sexism. We call for gender-collaborative training to be adopted by gender-segregated teams, and suggest that where there is resistance to any integration, teams start with mixed physical workouts and progress to mixed sport-specific training and then mixed competitive training. © The Author(s) 2020.
Keywords: adult; article; dept.soc; ethnography; female; human; interview; male; narrative; peer-reviewed; sexism; training

“Dad, wash your hands”: Gender, care work, and attitudes toward risk during the COVID-19 pandemic - Umamaheswar, Janani; Tan, Catherine (Socius: Sociological Research for a Dynamic World, 2020)
Recent analyses of responses to coronavirus disease 2019 (COVID-19) have posited that men’s dismissive attitudes toward the risks of the virus reflect their attempts to conform to masculine norms that valorize bravery and strength. In this article, the authors develop an alternative account of the gender differences in attitudes toward COVID-19. Drawing on three waves of in-depth interviews with college students and members of their households (n = 45) over a period of 16 weeks (for a total of 120 interviews), the authors find that men and women in comparable circumstances perceive similar risks of COVID-19, but they diverge in their attitudes toward, and responses to, these risks. Connecting scholarship on gender and care work with research on risk, the authors argue that gender differences in attitudes toward risk are influenced by the unique and strenuous care work responsibilities generated by the COVID-19 pandemic, which are borne primarily by women—and from which men are exempt. © The Author(s) 2020.
Keywords: COVID-19; care work; dept.soc; gender; pandemic; peer-reviewed; risk perception

The impact of faith-based narratives on climate change adaptation in narikoso, fiji - Bertana, Amanda (Anthropological Forum, 2020)
Most research on climate change in South Pacific island communities has privileged people’s observations of physical environmental change with less attention paid to how people interpret the causes of these changes. Increasingly, more studies are focusing on how communities are receiving messages about environmental degradation, and from whom they are receiving them. This case study draws upon ethnographic research conducted in November 2015 in Narikoso on Ono Island in Fiji’s Kadavu Group. This village was in the process of relocating inland as a response to shoreline erosion and severe coastal flooding. By employing data drawn from interviews with government actors, religious leaders, and residents of Narikoso village along with fieldnotes from participant observation, this paper examines how village residents interpreted coastal flooding and shoreline erosion according to the biblical story of Noah’s Ark alongside a secular narrative of climate change. I conclude by showing the unique challenges these worldviews had on the community’s decision to relocate. © 2020 The University of Western Australia.
Keywords: Fiji; Relocation; climate change adaptation; dept.soc; peer-reviewed; religion; sea level rise

“When the hell are you going to grow up?”: a life-course account of hybrid masculinities among incarcerated men - Umamaheswar, Janani (Journal of Developmental and Life-Course Criminology, 2020)
Purpose: Recent life-course scholarship has argued that desistance from (rather than persistence in) crime is a marker of adulthood. In this article, I argue that a commitment to desistance is only one of many elements of the participants’ sense of adult masculinity, which is best understood by drawing on theoretical literature on “hybrid masculinities.” By linking life-course criminological literature with recent theoretical advancements in the sociology of gender, I connect two important, but as yet independent, strands of research. Methods: Using the grounded theory approach to qualitative research, I performed inductive analyses of 24 in-depth interviews with adult men incarcerated at a state-run facility in the Northeastern USA. Results: I argue that the participants construct hybrid masculinities that combine conventionally masculine traits (such as being a provider and protector) with conventionally feminine traits (such as loyalty, humility, and emotional expressiveness). These hybrid masculinities manifest through the participants’ reliance on intangible markers of adulthood, and they emerge gradually over the men’s life course. I further argue that the disruptions that incarceration poses to the men’s life course impede their ability to realize their hybrid masculinities fully. Conclusion: The current research contributes to the burgeoning literature that attempts to correct the oversimplified portrayal of incarcerated men as singularly hypermasculine, and it also highlights how incarceration disrupts men’s life course, making it difficult for them to be the “hybrid” men that they wish to be. © 2020, Springer Nature Switzerland AG.
Keywords: Hybrid masculinity; Incarceration; Masculinity; Prison; The life course; dept.soc; peer-reviewed

“When my mother died, I think a part of me died:” maternal fusion and the relationship between incarcerated men and their mothers - Umamaheswar, J. (Journal of Family Issues, 2021)
Drawing on theoretical literature on the mothering discourse, I explore how incarcerated men give meaning to their relationships with their mothers. Using 24 in-depth interviews with incarcerated adult men, I argue that adherence to the mothering discourse results in sons holding their mothers’ maternal practices to impossibly high standards while simultaneously feeling obligated to reconcile with their mothers even when doing so is tremendously difficult. I also advance the concept of “maternal fusion”—the process through which the identities of mothers and their children are intertwined—to examine how incarcerated adult sons reproduce gendered mothering ideologies in their narratives of (a) negative early childhood and adolescent relationships with their mothers and (b) reconciliation as they reflect on their relationships with their mothers as adult sons.
Keywords: adolescent; adult; article; child; childhood; dept.soc; dept.swk; drawing; female; human; human experiment; ideology; incarceration; infant; interview; male; maternal fusion; mother; mothering; mothering discourse; narrative; peer-reviewed; theoretical study